Atherosclerosis-associated differentially methylated regions can reflect the disease phenotype and are often at enhancers. (January 2019) - Lacey, Michelle; Baribault, Carl; Ehrlich, Kenneth C.; Ehrlich, Melanie
Abstract: Background and aims: Atherosclerosis is a widespread and complicated disease involving phenotypic modulation and transdifferentiation of vascular smooth muscle cells (SMCs), the predominant cells in aorta, as well as changes in endothelial cells and infiltrating monocytes. Alterations in DNA methylation are likely to play central roles in these phenotypic changes, just as they do in normal differentiation and cancer. Methods: We examined genome-wide DNA methylation changes in atherosclerotic aorta using more stringent criteria for differentially methylated regions (DMRs) than in previous studies and compared these DMRs to tissue-specific epigenetic features. Results: We found that disease-linked hypermethylated DMRs account for 85% of the total atherosclerosis-associated DMRs and often overlap aorta-associated enhancer chromatin. These hypermethylated DMRs were associated with functionally different sets of genes compared to atherosclerosis-linked hypomethylated DMRs. The extent and nature of the DMRs could not be explained as direct effects of monocyte/macrophage infiltration. Among the known atherosclerosis- and contractile SMC-related genes that exhibited hypermethylated DMRs at aorta enhancer chromatin were ACTA2 (aorta α2 smooth muscle actin), ELN (elastin), MYOCD (myocardin), C9orf3 (miR-23b and miR-27b host gene), and MYH11 (smooth muscle myosin). Our analyses also suggest a role in atherosclerosis for developmental transcription factor genes having little or no previous association with atherosclerosis, such as NR2F2 ( COUP-TFII ) and TBX18 . Conclusions: We provide evidence for atherosclerosis-linked DNA methylation changes in aorta SMCs that might help minimize or reverse the standard contractile character of many of these cells by down-modulating aorta SMC-related enhancers, thereby facilitating pro-atherosclerotic phenotypic changes in many SMCs. Graphical abstract: Highlights: Preferential gain of atherosclerosis-linked DNA methylation at aorta enhancers. Hypermethylation at enhancers in some atherosclerosis-downregulated genes. Atherosclerosis-linked hyper- and hypomethylation have different functional associations. Smooth muscle cell phenotype changes explain their leukocyte-like DNA methylation. Important to consider enhancer epigenetic as well as promoter changes in disease.